Arbuscular mycorrhizal fungi enhanced resistance to low-temperature weak-light stress in snapdragon (Antirrhinum majus L.) through physiological and transcriptomic responses - Wei Li; Wei Li; Haiying Wu; Haiying Wu; Junkai Hua; Junkai Hua; Chengshang Zhu; Chengshang Zhu; Shaoxia Guo; Shaoxia Guo (Frontiers in Plant Science, 2024)
IntroductionLow temperature (LT) and weak light (WL) seriously affects the yield and quality of snapdragon in winter greenhouse. Arbuscular mycorrhizal fungi (AMF) exert positive role in regulating growth and enhancing abiotic stress tolerance in plants. Nevertheless, the molecular mechanisms by AMF improve the LT combined with WL (LTWL) tolerance in snapdragon remain mostly unknown.MethodsWe compared the differences in root configuration, osmoregulatory substances, enzymatic and non-enzymatic antioxidant enzyme defense systems and transcriptome between AMF-inoculated and control groups under LT, WL, low light, and LTWL conditions.ResultsOur analysis showed that inoculation with AMF effectively alleviated the inhibition caused by LTWL stress on snapdragon root development, and significantly enhanced the contents of soluble sugars, soluble proteins, proline, thereby maintaining the osmotic adjustment of snapdragon. In addition, AMF alleviated reactive oxygen species damage by elevating the contents of AsA, and GSH, and the activities of superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), ascorbate peroxidase (APX), dehydroascorbate reductase (DHAR), monodehydroascorbate reductase (MDHAR), and glutathione reductase (GR). RNA-seq analysis revealed that AMF regulated the expression of genes related to photosynthesis (photosystem I related proteins, photosystem II related proteins, chlorophyll a/b binding protein), active oxygen metabolism (POD, Fe-SOD, and iron/ascorbate family oxidoreductase), plant hormone synthesis (ARF5 and ARF16) and stress-related transcription factors gene (bHLH112, WRKY72, MYB86, WRKY53, WRKY6, and WRKY26) under LTWL stress.DiscussionWe concluded that mycorrhizal snapdragon promotes root development and LTWL tolerance by accumulation of osmoregulatory substances, activation of enzymatic and non-enzymatic antioxidant defense systems, and induction expression of transcription factor genes and auxin synthesis related genes. This study provides a theoretical basis for AMF in promoting the production of greenhouse plants in winter.